2012
DOI: 10.1186/1756-3305-5-285
|View full text |Cite
|
Sign up to set email alerts
|

Candidatus Neoehrlichia mikurensis in rodents in an area with sympatric existence of the hard ticks Ixodes ricinus and Dermacentor reticulatus, Germany

Abstract: BackgroundCandidatus Neoehrlichia mikurensis (CNM) has been described in the hard tick Ixodes ricinus and rodents as well as in some severe cases of human disease. The aims of this study were to identify DNA of CNM in small mammals, the ticks parasitizing them and questing ticks in areas with sympatric existence of Ixodes ricinus and Dermacentor reticulatus in Germany.MethodsBlood, transudate and organ samples (spleen, kidney, liver, skin) of 91 small mammals and host-attached ticks from altogether 50 small ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
5
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 39 publications
6
71
5
3
Order By: Relevance
“…Studies investigating rodents as well as questing ticks showed that prevalences in rodents were about 2-10 9 higher than in ticks (Obiegala et al 2014;Silaghi et al 2012). A reservoir function of rodents seems highly likely and was indeed proven in recent xenodiagnostic studies (Burri et al 2014).…”
Section: Occurrence and Geographical Distribution In Rodents And Othementioning
confidence: 95%
See 1 more Smart Citation
“…Studies investigating rodents as well as questing ticks showed that prevalences in rodents were about 2-10 9 higher than in ticks (Obiegala et al 2014;Silaghi et al 2012). A reservoir function of rodents seems highly likely and was indeed proven in recent xenodiagnostic studies (Burri et al 2014).…”
Section: Occurrence and Geographical Distribution In Rodents And Othementioning
confidence: 95%
“…It seems that insectivores do not play a role in the transmission or maintenance of Ca. N. mikurensis as so far none of the investigated insectivores were positive in Germany, Sweden and The Netherlands (Andersson and Raberg 2011;Jahfari et al 2012;Silaghi et al 2012).…”
Section: Occurrence and Geographical Distribution In Rodents And Othementioning
confidence: 96%
“…It has been detected in Mongolia [12], China [6,12,13], Japan [1,14], Russia [4,5,15,16], the Czech Republic [9,17,18], Slovakia [19][20][21], Moldova [22], Hungary [23][24][25], Austria [18,26], Germany [11,[27][28][29][30][31][32], Switzerland [33][34][35][36][37], Poland [38,39], Romania [40], France [28,41,42], Belgium [43], Italy [44][45][46], Spain [47], The Netherlands [3,42,43,48], and the Scandinavian countries [2,…”
Section: The Agentmentioning
confidence: 99%
“…I. ricinus and Dermacentor reticulatus have been shown to occur sympatrically (Silaghi et al, 2012), and the latter is currently spreading from east to west along river valleys in Poland and from south to north along the corridor of the Dyje and Morava rivers in the Czech Republic (Ć irokĂœ et al, 2011;Zygner et al, 2009). The Morava flows to the south, directly passing TBEV isolation sites at Zahorska Ves and Malacky in Slovakia to meet the Danube.…”
Section: Landscape-dependent Spread Patternsmentioning
confidence: 99%